Enhanced heavy oil recovery (SAGD), coinjection of steam and solvent, reduction of CEOR and CSOR. (19th March 2017) - Zare, Alireza; Abdulhameed, Faisal Muthanna; Hesland, Bjørnar; Hamouda, Aly A.
ABSTRACT: The effect of coinjection of hydrocarbon solvents (C4, C5, C6, C7, and C8 ), with steam at low pressure, on heavy oil recovery is addressed. It is concluded that the coinjection of solvents reduced cumulative steam oil ratio and the lighter solvents performed better in reducing cumulative net energy oil ratio (CEOR, GJ/m 3 ). The work illustrated that C6 was the best-performing solvent with respect to oil recovery (EOR) at 20 wt%, CEOR with an optimum of 30 wt%. An explanation on the reason for the highest EOR at 20 wt% is given. The coinjection with CO2 has also been addressed here with different schemes.